(untitled) (Research, Society and Development, 2021)
Introduction: Immune Checkpoint Inhibitors (ICI) block the inhibitory effects on receptors such as CTLA-4, PD-1 and PD-L1 and reestablish anti-tumor immunity. Thus, they are associated with gastrointestinal, dermatological, hepatic and endocrine Immune-Mediated Adverse Reactions (RAim). Objective: To analyze the profile of immune-mediated adverse reactions in cancer patients treated with immunological checkpoint inhibitors at a hospital in Salvador / Ba. Method: This is an observational, cross-sectional, retrospective study. All reports of adverse reactions associated with cancer treatment with ICIs, documented between January 2015 and May 2020, were evaluated. The research was approved by the Research Ethics Committee, according to the opinion number 4.074.757 / 2020. Results: During the study period, 27 patients used ICI. As for the RAim, 17 developed RAim. Of the most frequent RAim, 62% involved Nivolumab and 21% Pembrolizumab. 26% of RAim were gastrointestinal reactions, followed by 19% various reactions (such as vaginal bleeding and neuropathy); 53% of RAim were classified as moderate reactions. Among the therapeutic measures adopted to resolve RAIM, 73% of the ICI were discontinued and replaced by other chemotherapeutic agents; 53% of patients used supportive therapies to manage symptoms caused by Raim. As for the clinical outcome, 53% patients recovered from RAim, 24% recovered with sequelae and 23% died. Conclusion: The introduction of targeted therapy, adequate pharmacotherapeutic follow-up and monitoring by pharmacovigilance will favor the identification of immune-mediated adverse reactions, and the safe and appropriate use of ICI.